The Use of Comic Media to Increase the Maharah Qiraah of Elementary Education Level Students - Salamuddin Salamuddin; Sri Fadilah (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to improve the Arabic reading skills of grade VII-1 Tahfidz students at the Cipta Simpang Dolok College Foundation through Arabic comic media. This research is a classroom action research (Classroom Action Research). This research was conducted in the even semester of the 2021/2022 Academic Year, namely in May-June. The subjects in this study were students of class VII-1 Tahfidz Yayasan Pendidikan Cipta Simpang Dolok with a total of 31, consisting of 17 female students and 18 male students. The object of research is the students' reading skills. Research data were collected using a test given to each student. Based on the results of the percentage of student learning tests in the first cycle was 75.80% and in the second cycle increased to 87.19%. From the comparison of the two cycles, there was an increase of 11.39%. Thus, it can be concluded that reading skills (maharah Qira'ah) using comic media have increased.